Tolerability and pharmacokinetics of two antimony products after subcutaneous administration in dogs - Rambaldi, Julie; Barbarossa, Andrea; Morbidelli, Eva; Zaghini, Anna (The Journal of Infection in Developing Countries, 2018)
Introduction: Pentavalent antimony is the first choice drug for leishmaniasis in dog. Leishmaniasis has a complex pathogenesis and it manifests various clinical signs, some of which are often similar to those associated with the toxicity induced by antimonial treatment. Among the reasons for this toxicity, also a general problem of drug’s quality has been reported. Methodology: The general and local tolerability of two commercially available meglumine antimoniate based veterinary products was evaluated in 12 healthy dogs, 6 receiving Antimania (Fatro, Italy) and 6 receiving Glucantime (Merial, Spain), following repeated subcutaneous administrations of therapeutic doses for 14 days. Results: Individual and mean values of haematological and biochemical parameters in both groups remained in the physiological range, with no considerable differences within the two groups. The general tolerability of the drugs was also supported by clinical observations and physical examination of the dogs throughout the whole study period. Only slight local reactions at the injection sites, that spontaneously disappeared, were observed for both products starting from 12-84 hours after the administration. The pharmacokinetic parameters indicated no antimony accumulation. Conclusions: These results suggest that meglumine antimoniate administered at the recommended dosage regimen is well tolerated by healthy dogs, and that there is no significant difference between the two tested products.